EFFECTIVENESS OF PROJECT-BASED LEARNING TECHNOLOGIES IN TEACHING ENGLISH AT SCHOOL - Jurayev Asrorjon Mukhammadjonovich (American Journals, 2023)
Today, the school is working on the use of advanced educational technologies in teaching English, the use of nontraditional methods. This article describes several methods of effective teaching of English, as well as some of the modern educational technologies used in language learning.
Keywords: Language, English, independent language learning, educational technologies, project, interest, activity, interactive methods.